Fault tolerance in networked control systems under intermittent observations - Georges, Jean-Philippe; Theilliol, Didier; Cocquempot, Vincent; Ponsart, Jean-Christophe; Aubrun, Christophe (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an approach to fault tolerant control based on the sensor masking principle in the case of wireless networked control systems. With wireless transmission, packet losses act as sensor faults. In the presence of such faults, the faulty measurements corrupt directly the behaviour of closed-loop systems. Since the controller aims at cancelling the error between the measurement and its reference input, the real outputs will, in such a networked control system, deviate from the desired value and may drive the system to its physical limitations or even to instability.
Keywords: network congestion; fault-tolerant control; fault diagnosis; networked control systems; interacting multiple model